What’s new copycat? Creative interpretations of plagiarism in Finnish higher education - Moore, Erja (Septentrio Conference Series, 2020)
In Finland, all higher education institutions are committed to following a national policy to deal with suspected violations of good scientific practice. All suspicions of research misconduct are dealt with at the local level in the institution. If “the person alleged of misconduct or the instigator of the allegation” is dissatisfied with the decision, s/he may request a statement from the Finnish National Board on Research Integrity (2012, 36). The system has been claimed to be unique in the world. The responsibility of research misconduct investigations being on local level has led to a situation where the rector of the institution is responsible of the decisions resulting in differencesin local decisions, processes and definitions of plagiarism (Moore 2019). The data for this conference paper consist of 13 statements requested from Finnish National Boardon Research Integrity. All requests of statements dealt with suspicions of plagiarism in students’ Master’s theses. Thematic content analysis is used to typify first the interpretations of plagiarism and the investigation processes in institutions. The main result is that plagiarism is defined or denied on the local level and there is no need to comply with national or international definitionsof plagiarism. The national guidelines can be interpreted in creative ways: administrative and legal rhetoric is used to state that a thesis older than two years is not to be investigated at all, the instigator of the suspicion is not a party in a plagiarism case and therefore documentation of the investigation process can be kept internal. Secondary source plagiarism can be seen as plagiarism,but it can also be accepted as normal thesis writing. The national guidelines are interpreted differently resulting in creative, diverse and unequal interpretations of plagiarism.